Effect of Noise Pollution Exposure on Some Physiological and Immunological Parameters in Rabbit’s Blood - Kasim, Hala F.; Kadhum, Yasamin A. Amer; Rahman, Sabah A. Hameid A.; Abdulhameed, Jumana S.; Abdulhameed, Najat S. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The study comparatively evaluates the effect of Broadband white noise at 90dB intensity on hematological, sex hormones, immunoglobulins, lipid profile and biochemical parameters for five or 12 days using eighteen adult male and female rabbits. Noise exposure to rabbits caused a highly increase in its hematological parameters such as RBC, WBC, Hb, PLT, biochemical parameters such as (Glucose. Urea, Uric acid, Creatinine), lipid profile such as (Triglycerides and Cholesterol). Immunoglobulins such as (IgG and IgM) and Cortisol hormones, while sex hormones such as Estrogen and Testosterone level decreased significantly. The results indicated that the noise exposure could be harmful changes and can cause adverse effects to the body immune defense system.